2021
DOI: 10.1186/s13287-021-02461-z
|View full text |Cite
|
Sign up to set email alerts
|

Small blood stem cells for enhancing early osseointegration formation on dental implants: a human phase I safety study

Abstract: Background Small blood stem cells (SB cells), isolated from human peripheral blood, demonstrated the ability to benefit bone regeneration and osseointegration. The primary goal of our study is to examine the safety and tolerability of SB cells in dental implantation for human patients with severe bone defects. Methods Nine patients were enrolled and divided into three groups with SB cell treatment doses of 1 × 105, 1 × 106, and 1 × 107 SB cells, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…SB cells are small blood stem cells derived from adult blood. Aside from easy harvesting, distinguishable surface markers, and self‐renewability, these cells are also advantageous in regenerative medicine 48 . The self‐renewal and multipotent characteristics of MSCs facilitate the repair and regeneration of tissues.…”
Section: Tissue Engineering Innovations For Enhancing Osseointegrationmentioning
confidence: 99%
“…SB cells are small blood stem cells derived from adult blood. Aside from easy harvesting, distinguishable surface markers, and self‐renewability, these cells are also advantageous in regenerative medicine 48 . The self‐renewal and multipotent characteristics of MSCs facilitate the repair and regeneration of tissues.…”
Section: Tissue Engineering Innovations For Enhancing Osseointegrationmentioning
confidence: 99%
“…The trial, spanning six months, revealed no severe adverse effects, with observed improvements in bone mineral density (BMD) and stress levels. Elevations in specific cytokines and chemokines indicated SBSC-triggered responses for local tissue repair [ 46 ]. The findings support the well-tolerated use of SB cells in dental implantation, suggesting their potential for accelerating osseointegration in high-risk patients.…”
Section: Stromal Cell Populationmentioning
confidence: 99%
“…The dental pulp-derived MSCs are considered as a promising alternative cell source for bone regeneration since both in vitro and in vivo studies have shown that these cells reveal a high proliferation rate and a good osteogenic differentiation potential [41]. Similarly, peripheral blood-derived cells exhibited also bone regeneration efficiency [42].…”
Section: Cellsmentioning
confidence: 99%